Peran Pendidikan Pancasila dalam Menanamkan Nilai-Nilai Kebangsaan dan Mengatasi Dekadensi Moral di Kalangan Generasi-Z pada Era Digital - Mochammad Daffa Dzakwan Setiawan; Shafia Zahra; Indra Trinanda Darmawan; Raka Putra; Herli Antoni (Journal of Student Research, 2025)
Pancasila education has a strategic role in instilling national values and overcoming moral decadence among Generation Z, especially in the digital era. This research aims to analyze the contribution of Pancasila education in shaping the character and morality of Generation Z, identify the challenges faced in its implementation, and explore the role of family, school, and community as supporters. With a qualitative descriptive approach, data was collected through literature studies, interviews, and observations. The results of the study show that Pancasila education can strengthen the attitude of nationalism, tolerance, and love for the homeland among Generation Z. However, its implementation faces obstacles in the form of a lack of innovative learning methods, the impact of globalization, and the negative influence of information technology. The family and community play an important role in instilling Pancasila values through democratic parenting and a supportive social environment. This study recommends reforming the Pancasila education curriculum to be more relevant to the digital era, the use of technology-based interactive teaching methods, and collaboration between schools, families, and the community. It is hoped that the results of this research can be a strategic guide to create Generation Z who are characterful, moral, and ready to face global challenges while maintaining national identity.